Morpho-phylogenetic evidence reveals four novel species of Coniella (Diaporthales, Schizoparmaceae) from southern China - Duhua Li; Zixu Dong; Qiyun Liu; Yaling Wang; Zhaoxue Zhang; Xiuguo Zhang; Jiwen Xia (MycoKeys)
Coniella species are distributed worldwide and have been reported as plant pathogens, endophytes, or saprobes. In our ongoing survey of terrestrial plant fungi in southern China, we obtained Coniella isolates from diseased plant leaf tissues in Fujian, Hainan, and Yunnan provinces. Maximum likelihood and Bayesian inference based on four loci (ITS, LSU, rpb2, and tef1-α) were used to clarify the taxonomic placement of the species. We confirmed that they represent four new species, namely Coniella diaoluoshanensis, C. dongshanlingensis, C. grossedentatae, and C. veri based on both morphology and phylogeny support. The new species are compared with other Coniella species, comprehensive descriptions and micrographs are provided.